Predator (1987) [videorecording (DVD)] - McTiernan, John; Schwarzenegger, Arnold; Weathers, Carl; Carrillo, Elpidia; Duke, Bill, 1943-; Ventura, Jesse; Black, Shane (20th Century Fox Home Entertainment, 2018)
Waging an all-out war against an unseen enemy, a force more powerful and deadly than any on Earth-because the predator is not of this Earth.